Transnational cooperation of Turkish political parties as an ineffective tool of Europeanization. Issue 2 (2nd April 2016) - Wódka, Jakub
Abstract: This paper investigates the impact transnational cooperation with European Union (EU) partners has had on Turkish political parties – the ruling Justice and Development Party and the Republican People's Party. Two main platforms of transnational cooperation, i.e., affiliation with political families in the European Parliament and the workings of the EU–Turkey Joint Parliamentary Committee, are scrutinized. The article posits that transnational cooperation with partners on a European level has had a limited – if any – socialization effect on Turkish political organization. This stems mainly from ideological divergences between Turkish political parties and their European counterparts, EU scepticism which permeates political elites in Turkey as well as rising anti-Turkish sentiments within the EU establishment.